2019
DOI: 10.1111/jcmm.14773
|View full text |Cite
|
Sign up to set email alerts
|

VEGF signalling enhances lesion burden in KRIT1 deficient mice

Abstract: The exact molecular mechanisms underlying CCM pathogenesis remain a complicated and controversial topic. Our previous work illustrated an important VEGF signalling loop in KRIT1 depleted endothelial cells. As VEGF is a major mediator of many vascular pathologies, we asked whether the increased VEGF signalling downstream of KRIT1 depletion was involved in CCM formation. Using an inducible KRIT1 endothelial‐specific knockout mouse that models CCM, we show that VEGFR2 activation plays a role in CCM pathogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…The research community has identified a number of different signaling pathways dysregulated following loss of the CCM genes: RhoA/ROCK [15][16][17][18], MEKK3-KLF2/4 [19][20][21], ICAP-1 and β1 integrin [22,23], DELTA-NOTCH [24], angiopoietin-2 [25], thrombomodulin and endothelial protein C receptor [26], reactive oxygen species (ROS) [27], autophagy [28], and endothelial-to-mesenchymal transition (EndMT) [29]. A nearly equal number of therapeutics have also been proposed or tested in CCM models: statins [15], fasudil [30], TGF-β inhibitors [29], sulindac [31], tempol [32], vitamin D 3 [32], angiopoietin-2 neutralizing antibody [25], fluvastatin and zoledronate [33], indirubin-3′-monoxime [34], thrombospondin1 replacement [35], propranolol [36,37], ponatinib [38], BA1049 [39], and VEGFR2 inhibitor [40]. Several of these compounds arose from unbiased, high-throughput in vitro and in vivo screens of libraries containing thousands of compounds [32][33][34].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research community has identified a number of different signaling pathways dysregulated following loss of the CCM genes: RhoA/ROCK [15][16][17][18], MEKK3-KLF2/4 [19][20][21], ICAP-1 and β1 integrin [22,23], DELTA-NOTCH [24], angiopoietin-2 [25], thrombomodulin and endothelial protein C receptor [26], reactive oxygen species (ROS) [27], autophagy [28], and endothelial-to-mesenchymal transition (EndMT) [29]. A nearly equal number of therapeutics have also been proposed or tested in CCM models: statins [15], fasudil [30], TGF-β inhibitors [29], sulindac [31], tempol [32], vitamin D 3 [32], angiopoietin-2 neutralizing antibody [25], fluvastatin and zoledronate [33], indirubin-3′-monoxime [34], thrombospondin1 replacement [35], propranolol [36,37], ponatinib [38], BA1049 [39], and VEGFR2 inhibitor [40]. Several of these compounds arose from unbiased, high-throughput in vitro and in vivo screens of libraries containing thousands of compounds [32][33][34].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Since their development, the inducible CCM alleles have required deletion during the first three days of life to induce CCMs. Postnatal developmental angiogenesis in the cerebellum and retina is a strong sensitizer of CCM formation [62] and the inhibition of angiogenesis, with multiple different therapies, reduces CCM formation [25,40]. We hypothesized that deleting Pdcd10 later in developmental angiogenesis may lead to a reduced CCM burden that is conducive to drug studies lasting several weeks.…”
Section: Delaying Pdcd10 Deletion Delays Ccm Formation and Extends Thmentioning
confidence: 99%
“…The CCMs that develop in these inducible models occur nearly exclusively in the cerebellum, suggesting a strong sensitizing role of angiogenesis. Inhibition of vascular endothelial growth factor (VEGF) signaling with SU5416, a VEGFR2 specific antibody, in an inducible CCM1 mouse model reduced CCM formation and hemorrhage [40]. By contrast, an exploratory biomarker study found plasma levels of VEGF to be lower in CCM patients who had a hemorrhage in the past 3 months when compared to CCM patients without hemorrhage [68].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic CCM hemorrhage is a hallmark feature of the human disease for which few animal models exist for therapeutic testing [53,51,52,58] . Very few studies have been able to use an inducible CCM mouse model to study a chronic CCM hemorrhage, none of which have been with the more aggressive CCM3 mouse model [40]. One reason for the paucity of studies measuring chronic hemorrhage is the need to conduct experiments over several months for the chronic hemorrhage phenotype to develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation